The Effect Of Employee Engagement, Leadership, And Welfare On Employee Performance At Fatimah Islamic Hospital Banyuwangi - Donny Firmansyah; Mundakir; Sukadiono; Pipit Festi (LP2IHKI UMSurabaya, 2025)
Objective: This study aimed to analyze the effects of employee engagement, leadership, and welfare on employee performance at Fatimah Islamic Hospital Banyuwangi. The study also identified which variables had the strongest contribution to employee performance improvement outcomes. Method: This study used a descriptive quantitative design. Data were collected through questionnaires distributed to all 70 employees of Fatimah Islamic Hospital Banyuwangi. Respondents represented outpatient, inpatient, pharmacy, medical records, and administrative units. Data were analyzed using multiple linear regression with SPSS version 26 software. Results: Simultaneously, employee engagement, leadership, and employee welfare had a significant effect on employee performance (F = 67.315; p < 0.001) with a coefficient of determination of 74.8% (R² = 0.748). Partially, employee engagement had a significant positive effect (β = 0.450; p < 0.001), and employee welfare also had a significant positive effect (β = 0.380; p < 0.001). Leadership showed a positive but statistically non-significant effect (β = 0.120; p > 0.05). Conclusion: Employee engagement and employee welfare were the dominant factors affecting employee performance. Therefore, hospital management should prioritize engagement improvement, effective welfare programs, continuous supervision, regular evaluation, staff motivation, and leadership development to improve service quality and organizational performance sustainably in future services